2001
DOI: 10.1097/00005392-200112000-00123
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Structured Withdrawal Program to Prevent Relapse of Nocturnal Enuresis

Abstract: The structured withdrawal program significantly reduces relapse rates, and offers an alternative and rapid means of successfully withdrawing medication. It is argued that the influential variable concerns the ability of the child to shift attribution for success from an external source (that is medication) to an internal focus (that is changes in themselves).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…excluding studies where additional procedures were coupled with the alarm), a success criterion of 14 consecutive dry nights was adopted, children were treated for at least 6 weeks and those with both day-and night-time wetting were excluded, found a relapse rate of 42% in 213 successfully treated children. This is a significant figure and highlights the need for regular monitoring following treatment and the utilization of relapsepreventing measures such as over-learning [52] or internalization of success [53].…”
Section: Discussionmentioning
confidence: 99%
“…excluding studies where additional procedures were coupled with the alarm), a success criterion of 14 consecutive dry nights was adopted, children were treated for at least 6 weeks and those with both day-and night-time wetting were excluded, found a relapse rate of 42% in 213 successfully treated children. This is a significant figure and highlights the need for regular monitoring following treatment and the utilization of relapsepreventing measures such as over-learning [52] or internalization of success [53].…”
Section: Discussionmentioning
confidence: 99%
“…Timedependent approaches administer constant doses of medication with increasing time intervals [51,58], whereas dosedependent approaches decrease the doses of desmopressin after constant time intervals [6,15,16,36,37,53,59e63]. A tendency for lower relapse rates associated with superior long-term success rates following the time-dependent approach was apparent (Table 8).…”
Section: Sudden Termination Versus Structured Withdrawal Programsmentioning
confidence: 99%
“…These results could be biased by the fact that only two studies investigated the time-dependent approach. Furthermore, with respect to time-dependent structured withdrawal programs, conflicting long-term success rates resulted (53.1% [58] vs 90.2% [51]). It has also to be taken into account that Butler et al applied a fixed scheme, whereas the algorithm of Marschall-Kehrel et al flexibly reassigned patients to the previous time-triggered pattern.…”
Section: Time-versus Dose-dependent Structured Withdrawal Programsmentioning
confidence: 99%
“…A Cochrane review also concluded that desmopressin rapidly reduces the number of wet nights, but that limited evidence from short-term trials in small numbers of patients suggests this effect may not be sustained after treatment withdrawal [22]. Longer-term trials, though uncontrolled, indicate improved maintenance effects however [23], and evidence is mounting that structured withdrawal of medication may encourage the persistence of improvements [24]. In a recent randomized controlled study, abrupt withdrawal was compared with structured withdrawal.…”
Section: Introductionmentioning
confidence: 99%